2003
DOI: 10.1248/bpb.26.1120
|View full text |Cite
|
Sign up to set email alerts
|

Glucurono- and Sulfo-Conjugation of Kaempferol in Rat Liver Subcellular Preparations and Cultured Hepatocytes

Abstract: The health benefits of flavonoids as preventive nutrition from coronary heart disease and cancer have received considerable attention since they occur naturally in dietary plants. 1,2) For a better understanding of the pharmacological activity of flavonoids, a thorough knowledge of their metabolism in the body is required. Flavonoids are polyphenols and, therefore, considered to be metabolized mainly as conjugated derivatives by coupling with a glucuronic acid or a sulfuric acid during the phase II biotransfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The effect of conjugation on biological activities remains to be investigated. No sulfoconjugates were detected in this experiment by LC/MS n and specific enzymatic hydrolysis (␤-glucuronidase-sulfatase/D-saccharic acid 1,4-lactone) methods (Yodogawa et al, 2003), probably because of the inhibitory effect of scutellarein on phenol sulfotransferase (Walle et al, 1995). There has been some controversy regarding how flavonoids are absorbed, and it has been suggested that some flavonoids, mainly those with glucose molecules, might be absorbed intact (Hollman et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The effect of conjugation on biological activities remains to be investigated. No sulfoconjugates were detected in this experiment by LC/MS n and specific enzymatic hydrolysis (␤-glucuronidase-sulfatase/D-saccharic acid 1,4-lactone) methods (Yodogawa et al, 2003), probably because of the inhibitory effect of scutellarein on phenol sulfotransferase (Walle et al, 1995). There has been some controversy regarding how flavonoids are absorbed, and it has been suggested that some flavonoids, mainly those with glucose molecules, might be absorbed intact (Hollman et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
“…Although the in vitro and in vivo experiments revealed that the glucurono-or sulfo-conjugated metabolites could occur at any hydroxyl group of flavonoids, the 7-OH position on the A-ring is predominantly conjugated to form a glucuronide or sulfate compared with 3-and 5-OH positions (Boersma et al, 2002;O'Leary et al, 2003;Yodogawa et al, 2003;Gradolatto et al, 2004; (Zhang and Brodbelt, 2004), the major metabolites in rat urine were 4Ј-Oglucuronide, followed by 7-O-glucuronide. Because of the low acidity, the 5-OH position was well known to be the least reactive for glucuronidation.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that flavonols undergo metabolism, i.e., glucuronidation and/or sulfation in the body. 19) A conjugation position-specific effect of quercetin metabolites on AhR transformation has been reported. 20) Thus not only kaempferol aglycone but its metabolites might suppress AhR transformation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that flavonoids exist as aglycones, glucuronic acid conjugates, and sulfonic acid conjugates in plasma (Manach et al, 1996;Yodogawa et al, 2003;Silberberg et al, 2005). So the plasma samples should be acid hydrolytic to transform conjugates to aglycones.…”
Section: Fig 2 Daughter Ion Mass Spectra Of the Analytes In Gbts Andmentioning
confidence: 99%